TYPE OF THE AUTHOR IN NON-REFERENT POETRY - Derkachova, O.S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The types of the author in the modern Ukrainian poetry are characterized. Non-referent poetry is highlighted. Two types of the author are distinguished; they are the author-trickster and the author-artist. Their differences and common features are defined.